रोगव्याधि, दोष निवारण र लामो आयुका देवता कुम्भेश्वर {Kumbesheswor the Deity of Long-life, Remover of Illness and Defects} - KC, Shyam Madan (Nepalese Culture, 2023)
Kumbheshwar Temple of Patan has been famous since ancient times, but it has not been thoroughly studied. A study has been done to highlight the cultural significance of this temple. In it, the history, architecture and worship methods of the temple have been studied. A qualitative method has been adopted in this. Qualitative data is collected from observation, Interview, group discusses, key informant and published and unpublished book, Journal, Report. The data has been analyzed through inductive method. This temple was famous since ancient times. Inside the temple there is a big Sarveshwar image of small five-faced Shivlinga Kumbheshwar. This is a Nepali style temple has five floors built on a three-level plinth. There are 108 Bhairavas on the Tundals (struts). The roof of the temple is supported by 6-6 struts in all four directions of the temple and four struts at the four corners. Nitya Puja (everyday worship) and other regular pujas are performed withen the temple every day. On Mukhashtami, it is customary to crown the Panchabuddha created by Tamadhara on the Kumbheshwar Shivling. On Guru Purnima, Nagainag is seen wearing the crown of Vere. Those who become new Jhakris (Shaman) offer water from Gosai Kund to Kumbheshwar. Sage Agastya (saint) is believed to have founded Kumbheshwar. People go to Kumbheshwar to get long-life, diseases and defects. The study brings to light that Kumbheshwar is an ancient temple.